2016
DOI: 10.1016/j.immuni.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced CD300b Receptor Binding to Toll-like Receptor 4 Alters Signaling to Drive Cytokine Responses that Enhance Septic Shock

Abstract: SUMMARY Receptor CD300b is implicated in regulating the immune response to bacterial infection by an unknown mechanism. Here, we identified CD300b as an lipopolysaccharide (LPS)-binding receptor and determined the mechanism underlying CD300b augmentation of septic shock. In vivo depletion and adoptive transfer studies identified CD300b-expressing macrophages as the key cell type augmenting sepsis. We showed that CD300b, and its adaptor DAP12, associated with Toll-like receptor 4 (TLR4) upon LPS binding, thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 43 publications
0
77
0
Order By: Relevance
“…TLR4 endocytosis from the cell surface requires Syk-PLCγ2 signaling (52). Another report suggested a role for the C330b-DAP12-TLR4-Syk-PI3K signaling complex in amplifying inflammatory responses in macrophages (53). A role for Syk in the regulation of TLR signaling in pDCs is also observed (54).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 endocytosis from the cell surface requires Syk-PLCγ2 signaling (52). Another report suggested a role for the C330b-DAP12-TLR4-Syk-PI3K signaling complex in amplifying inflammatory responses in macrophages (53). A role for Syk in the regulation of TLR signaling in pDCs is also observed (54).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a role for CD300b in binding LPS and associating with TLR4 and CD14 was suggested (Fig. 1B) [36]. CD300b promoted activation of the TRIF pathway and IFNβ production, and suppressed MyD88-dependent activation of ERK1/2, collectively leading to reduced production of anti-inflammatory IL-10 and increased inflammatory cytokines.…”
Section: Phosphoinositide Regulation Of Tlr4 Signalingmentioning
confidence: 99%
“…Syk activation induces the phosphorylation of Akt, and the activation of phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) (Fig. 1B) [36]. Interestingly, after LPS-stimulation, TIRAP-MyD88 interaction with TLR4 was decreased in a CD300b-dependent manner, suggesting a deficiency in myddosome formation.…”
Section: Phosphoinositide Regulation Of Tlr4 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…CD300F can both stimulate and inhibit efferocytosis depending on the type of phagocyte, and CD300F-deficient mice develop symptoms of autoimmunity (87). CD300B signaling via the adaptor protein DAP12 positively regulates efferocytosis, and Voss et al recently showed that LPS treatment of macrophages causes CD300B to interact with TLR4 and that this interaction augments TLR4-dependent production of pro-inflammatory cytokines (88). Along these lines, the CD300F receptor was recently shown to interact directly with the common chain of IL-4/IL-13 receptor to enhance production of IL-4 and thus could potentially promote M2 polarization in macrophages (89).…”
Section: Introductionmentioning
confidence: 99%